Interannual variability of Greenland winter precipitation sources: Lagrangian moisture diagnostic and North Atlantic Oscillation influence - Sodemann, H.; Schwierz, C.; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Journal of Geophysical Research: Atmospheres, 2008)
ISSN:0148-0227 ISSN:2169-897X